THE EFFECTIVENESS OF USING PICTURE SERIES MEDIA ON STUDENT’S WRITING NARRATIVE TEXT - Habibatul Maula Romadlona; Zanuba Arifah Khofshoh (Karangan: Jurnal Bidang Kependidikan, Pembelajaran, dan Pengembangan, 2023)
The purpose of the research was to determine how the use of picture series media to write narrative text skills. Subjects were students of class VIII PK MTs. Ma’arif NU Nguwok. The research used is a pre- experimental quantitative research using serial picture media in improving the ability to write narrative texts for class VIII PK MTs. Ma'arif NU Nguwok with 21 students. The instrument used in this research is a narrative text writing test sheet with the help of a series of pictures. Based on the results of study, concludes that picture series media to improve students' writing skills in daily life is effective for improving students' writing skills. From the analysis of research data, it can be concluded that the students' writing ability in the 2020/2021 school year is good. This is evidenced by the average value of the percentage according to aspects of 80.47% with good criteria.